PENGARUH ANALISIS RASIO KEUANGAN PADA KINERJA KEUANGAN PEMERINTAH PUSAT TERHADAP AKUNTABILITAS PELAPORAN KEUANGAN - Annisaul Mardhiyah; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
The purpose of this research is to determine whether the financial performance of the central government as an independent variable, proxied by solvency ratios, revenue effectiveness, revenue growth, and expenditure growth, affects the accountability of financial reporting, which is proxied by the BPK's opinion as a dependent variable. The BPK's opinion consists of Unqualified Opinion (WTP), Qualified Opinion (WDP), Adverse Opinion (TW), and Disclaimer of Opinion (TMP).The data analyzed are government financial statements, specifically the audited financial statements of central ministries for the years 2017-2021. The research data consists of secondary data obtained by downloading from the BPK RI website. The population of this research consists of 34 financial statements of state ministries that have been audited by the BPK and their audit reports. The sample in this study uses the entire sample of 170. Data analysis used multiple linear regression analysis. The research results show that the government's financial performance in terms of solvency, revenue effectiveness, and expenditure growth does not affect the accountability of financial reporting. For financial performance in the form of revenue growth, it has an impact on the accountability of financial reporting.